Platinum supported on hydroxyl-grafted poly (3, 4-ethylenedioxythiophene)-modified RuCo, N-tridoped bamboo-like carbon nanotubes for direct methanol fuel cell. (8th February 2023) - Liu, Lielie; Jamal, Ruxangul; Abdiryim, Tursun; Ma, Yuguo; Liu, Xiong; Zou, Dongna; Liu, Haile; Song, Yanyan
Abstract: The development of highly active and efficient heterogeneous catalytic oxidation system has become an attractive research field. In this paper, a catalyst (RuCo/N-CNT@PEDOT-OH/Pt) from platinum nanoparticles (Pt NPs) supported on hydroxyl-grafted poly(3, 4-ethylenedioxythiophene) (PEDOT–OH)-modified RuCo, N-tridoped bamboo-like carbon nanotubes (RuCo/N-CNT) are used for direct methanol fuel cell (DMFC). The electrocatalytic activity of RuCo/N-CNT@PEDOT-OH/Pt is systematically compared with RuCo/N-CNT/Pt (Pt NPs supported on RuCo/N-CNT without PEDOT-OH) in the methanol oxidation reaction (MOR). The growth mechanism of carbon nanotubes and the role of heteroatom doping in the electrocatalytic process is explored. The catalysts show excellent electrocatalytic performance with high stability for MOR. It is found that the mass activity (MA) of the RuCo/N-CNT@PEDOT-OH/Pt (1961.3 mA mg −1 Pt ) for MOR was higher than that of RuCo/N-CNT/Pt (1470.1 mA mg −1 Pt ) and the commercial Pt/C catalysts (281.0 mA mg −1 Pt ), indicating the positive effect of the PEDOT-OH in the electrocatalytic MOR. In addition, density functional theory (DFT) calculations verify the possible mechanism pathways of the obtained RuCo/N-CNT@PEDOT-OH/Pt catalyst. This presented catalyst offers new inspiration for designing efficient electrocatalysts for methanol oxidation. Highlights: Three-dimensional structured RuCo/N-CNT@PEDOT-OH/Pt is used for MOR. The catalyst has high catalytic activity of 1961.3 mA mg −1 Pt for MOR. The synergistic effect of Pt, RuCo/N-CNT and PEDOT-OH is studied. DFT theory demonstrates and explains the experimental results.